The Influence of Organizational Activity, Motivation and Discipline through Self Efficey on Learning Achievement - Sari, Syanita; Khafid, Muhammad; Widiyanto, Widiyanto (Universitas Negeri Semarang, 2024)
Learning achievement is the result achieved by a person to achieve predetermined goals. This study is to test organizational activity, learning motivation and learning discipline on student learning achievement by presenting self-efficiency as an intervening variable. In addition, seven hypotheses were proposed in this study to ascertain whether the independent variables of organizational activeness have a direct influence on each other, learning motivation and learning discipline, through intervening variables of self-efficiency on the dependent variable of learning achievement. The population in quantitative research amounted to 381 students of Economic Education, Semarang State University in 2020. A sample of 195 respondents from Semarang State University Economic Education was selected using proportional random sampling method. Data collection using questionnaires, descriptive statistical data analysis, and path analysis. The results of this study show: (1) organizational activity has a direct influence on learning achievement positively and insignificantly, (2) direct influence of learning motivation on learning achievement positively and significantly, (3) direct influence of learning discipline on learning achievement positively and significantly, (4) direct influence of self efficiency On learning achievement positively and significantly, (5) the direct influence of organizational activity on learning achievement through self efficiency positively and significantly, (6) the direct influence of learning motivation on learning achievement through self efficiency positively and significantly , (7) the direct influence of learning discipline on learning achievement through self efficiency positively and significantly.